Pengaruh Debt Covenant, Pertumbuhan Perusahaan, dan Ukuran Perusahaan terhadap Manajemen Laba dengan Kepemilikan Manajerial Sebagai Variabel Moderasi pada Bank Umum Syariah Indonesia - Khusna, Annuria Khoridatul; Nurhadi, Bayu (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this study was to determine the effect of debt covenants, company growth and company size on earnings management with managerial ownership as a moderating variable. The population in this study are Islamic commercial banks listed on the Financial Services Authority for the period 2016 - 2022. Sampling in this study used purposive sampling method with 9 banks from 13 banks. The results showed that debt covenant affects earnings management, company growth variables affect earnings management, while company size variables affect earnings management. Managerial ownership can moderate the effect of debt covenant on earnings management, but cannot moderate the effect of company growth and company size on earnings management..